Respuesta :

4(2s − 1) = 7s + 12

Multiply the bracket by 4

(2s)(4)(-1)(4)= 7s+12

8s-4= 7s+12

Move 7s to the other side. Sign changes from +7s to -7s.

8s-7s-4= 7s-7s+12

8s-7s-4= 12

Move -4 to the other side. Sign changes from -4 to 4.

8s-7s-4+4= 12+4

8s-7s= 16

s= 16

Answer: s= 16

Answer: [tex]s=16[/tex]

Step-by-step explanation:

Given the following equation:

[tex]4(2s-1) = 7s + 12[/tex]

You need to solve for "s" in order to find its value:

- Apply Distributive Property:

[tex]8s-4 = 7s + 12[/tex]

- Add 4 to both sides of the equation:

[tex]8s-4+4 = 7s + 12+4\\\\8s=7s+16[/tex]

- Finally, subtract [tex]7s[/tex] to both sides of the equation:

[tex]8s-7s=7s+16-7s\\\\\\\\s=16[/tex]

ACCESS MORE